64Traditional Japanese Diet Score and cancer incidence and mortality - a 23-year longitudinal global study. (2nd September 2021) - Abe, Chisato; Imai, Tomoko; Sezaki, Ayako; Miyamoto, Keiko; Kawase, Fumiya; Shirai, Yoshiro; Inden, Ayaka; Kato, Takumi; Sanada, Masayo; Shimokata, Hiroshi
Abstract: Background: Traditional Japanese diets are considered to be one cause of Japanese health and longevity. We created a Traditional Japanese Diet Score (TJDS) and investigated the relationship between the TJDS and cancer during more than 20 years using global database. Methods: Total cancer incidence and mortality by country were identified from the Global Burden of Disease 2017 database. Average food supply (g/day/capita) and energy supply (kcal/day/capita) by country were obtained from the Food and Agriculture Organization of the United Nations database. The TJDS by country was calculated from nine food groups, the higher scores mean the more adherence to traditional Japanese diet. That is beneficial food groups (rice, fish, soybeans, vegetables, eggs, seaweed) gave positive points to high supply amount, and food groups not commonly used in the Japanese diet (wheat, milk, and red meat) gave minus points to high supply amount. The longitudinal associations between the TJDS and cancer incidence and mortality controlled for covariates were examined during 23 years from 1990 to 2013. The country covered by this study was 139 countries with populations of 1 million or greater. Results: The TJDS was negatively associated with cancer incidence and mortality longitudinally in a linear mixed-effect model controlled for covariates. Conclusions: These results suggest that greater adherence with the TJDS supressed cancer incidence and mortality worldwide. Key messages: Well-balanced eating habits like traditional Japanese diets is important for suppressing cancer.